Praktik Mobile Journalism dalam Peliputan Jurnalis Voice of America di Indonesia - Aryana Catur Rangga; Firmansyah; Dadi Ahmadi (Bandung Conference Series: Journalism, 2023)
Abstract: The rapid development of the times, affecting all forms of change and progress for society. Technological transformation in the field of communication and information dissemination is one of those affected by these changes. Cellphones or cell phones are a means of communication technology in the production of content. Mobile Journalism (MOJO) can be unique in terms of convergence and multimedia in journalistic practice professionally. MOJO practice is implemented by media companies with different practices, one of which is the Voice of America media, the Indonesian bureau. Using a qualitative research methodology and a constructivist paradigm, researchers explore how technology determines VOA journalists in the Reductionistic, Monistic, Neutralizing, and Technological Imperative spheres. MOJO is dissected through the case study method according to Robert E. Stake. Qualitative data analysis was carried out by interviews, document analysis, and observation. The results of the study show that MOJO helps journalists simplify their tasks, especially in the technical aspects. But it's not without drawbacks, for example coverage using a smartphone result not as good as if using a professional camera. In addition, the use of smartphones during coverage often gives an unprofessional impression, thereby affecting the trustworthiness of the informants during coverage. Abstrak: Perkembangan zaman secara pesat, memengaruhi segala bentuk perubahan dan kemajuan bagi masyarakat. Transformasi teknologi di bidang komunikasi dan penyebaran informasi menjadi salah satu yang terkena dampak perubahan tersebut. Handphone atau telepon genggam menjadi salah satu alat teknologi komunikasi dalam produksi sebuah konten. Mobile Journalism (MOJO) dapat menjadi keunikan tersendiri dari segi konvergensi dan multimedia pada praktik jurnalis secara profesional praktik MOJO diimplementasikan oleh perusahaan media dengan praktik yang berbeda-beda, salah satunya media Voice of Amerika biro Indonesia. Penelitian berparadigma konstruktivis dengan metodologi penelitian kualitatif, yakni mengeksplorasi bagaimana praktik mobile journalism pada jurnalis VOA. MOJO dibedah melalui metode studi kasus menurut Robert E. Stake. Analisis data kualitatif dilakukan dengan wawancara, analisis dokumen, dan observasi. Hasil dari penelitian menunjukkan bahwa MOJO membantu para jurnalis menyederhanakan tugas mereka khususnya dalam aspek teknis, melalui smartphone, seorang jurnalis bisa merekam dan/atau menyiarkan langsung peristiwa dari smartphone mereka. Namun bukan tanpa kekurangan, misalnya liputan menggunakan smartphone hasil video dan audionya tak sebagus jika menggunakan kamera profesional. Selain itu penggunaan smartphone saat liputan seringkali memberikan kesan tidak profesional sehingga mempengaruhi kepercayaan narasumber saat liputan.